Incorporation of nomina of higher-ranked taxa into the International Code of Zoological Nomenclature: the nomenclatural status of class-series zoological nomina published in a non-latinized form - Dubois, Alain (Zootaxa, 2009)
Many new higher-ranked taxa are currently recognized by taxonomists as a result of the numerous phylogenetic hypotheses which are regularly published. The absence in the Code of Rules for the nomenclature of taxa above the rank superfamily (class-series nomenclature) is a factor of growing chaos in zoological taxonomy. This is why Dubois (2005) proposed a set of formal Rules for this nomenclature, which should be discussed and considered for incorporation into the Code. This paper focuses on a particular point regarding these proposed Rules, i.e., whether class-series nomina should be considered nomenclaturally available from their first publication in any modern language, provided they were latinized subsequently, or only from their first use in a latinized form. It is argued that the first solution should be retained, not only “to render unto Caesar the things which are Caesar’s”, but also for simple internal consistency within the Code. According to the Rules of the Code, generic nomina may be available, with their original authors and dates, even if directly transferred unchanged from modern languages, and family-series nomina, first published in a nonlatinized form, may be available, with their original authors and dates, provided they have been subsequently latinized. These general statements are illustrated with the higher nomenclature of several taxa including amphibians. According to the proposed Rules, the following nomina, authors and dates are the valid ones for the taxa they designate: VERTEBRATA Cuvier, 1800; AMPHIBIA De Blainville, 1816; GYMNOPHIONA Rafinesque-Schmaltz, 1814; BATRACHIA Brongniart, 1800; ANURA Duméril, 1806; URODELA Duméril, 1806; AMPHIPNEUSTA Merrem, 1820.